Construction and inspection of floor joists - International Code Council ([Illinois] : International Code Council, 2003)
Discusses the provisions for floor joists for structures that are generally associated with structures built using conventional light-frame construction methods
Protection against decay and termites -- Spans and spacing -- Joist bearing, lapping or splicing -- Blocking and other lateral support -- Cutting, notching and boring holes -- Openings -- Joists supporting bearing partitions -- Fastening of joists -- Draft stopping and fireblocking -- Trusses
Title from title screen
Title on workbook: IRC 2000/2003 workbook: Construction and inspection of floor joists
DVD format
Keywords: Wooden-frame buildings; Floors -- Law and legislation; Floors -- Design and construction; Building inspection -- United States; Building laws -- United States